Trade opportunities in textiles between India and BRICS: A structural share-based analysis - Lalitha , N (Asian Journal of Economics and Empirical Research, 2025)
As India adjusts to the changing international trade scenario brought about by the reciprocal tariffs imposed by the U.S. government, there is a need to identify product groups and markets with strong export potential for Indian goods. India is one of the top textile exporters in the world and enjoys an immense comparative advantage in textile exports, as reflected in the high Revealed Comparative Advantage (RCA) Index. BRICS is a grouping of emerging economies, and as of 2025, these countries together accounted for 41 percent of the world population, 24 percent of the total world GDP, and 16 percent of the world trade. We evaluated the trade complementarity between India and the BRICS countries Brazil, Russia, China, and South Africa in textiles from 2001 to 2023 to examine the alignment between India’s export specialization and the import needs of these countries. The study found that the trade complementarity index with Russia and South Africa was higher than that with Brazil and China for almost the entire study period. Despite high trade complementarity, the share of Russia and South Africa in India’s major exports grew less rapidly than that with Brazil and China. This study provides an approach to identify trade opportunities in textile product groups by combining four key indicators: trade complementarity (supply–demand alignment), growth in the product group's share in India’s exports (supply potential), growth in the product group's share in the partner country's imports (demand trend), and growth in the partner’s share in India’s exports.